KEKOSMOPOLITAN PETANI DALAM PENGELOLAAN USAHATANI TANAMAN PADI SAWAH DI DESA LAMOOSO KECAMATAN ANGATA KABUPATEN KONAWE SELATAN - Hasniati, Hasniati (Jurnal Akrab Juara, 2019)
The purpose of this research was to determine (1) Farmers Cosmopolitan Management of farm and (2) related cosmopolitan farmers with management farm of lowland rice in Lamooso Village. The observed variables is farmers cosmopolitan and management of lowland rice farming. The population in this research was farmers amounted to 209 people, were taken simple random sampling with the determination of total sample of 31 people. the data that was obtained in quantitative analysis. The result showed that: (1) cosmopolitan farmers classified in the high category (2) management of lowland rice classified in the category of being and (3) farmers cosmopolitan in the case of, contact the extension, reading bulletin or magazine agriculture, listening to radio or watching television are significant correlation with management of lowland rice farming in Lamooso Village sub-district Angata, Regency South Konawe Rigency.